Design and evaluation of the target spray platform. (4th March 2021) - Zhou, Mingchuan; Jiang, Huanyu; Bing, Zhenshan; Su, Hang; Knoll, Alois
The target-oriented spraying is an effective way to minimize chemical input in agricultural production and it is important to actualizing sustainable agriculture. This article focused on the design and optimization of the target spray platform. The spray platform consists of three parts: the vision system, the spray system, and the moving platform. All components were effectively connected and preliminarily evaluated especially regarding the response time and target spray accuracy. A simulation system was built considering the real crop geometric shape and nozzle spray pattern using the Monte Carlo method. The spray simulator was used to optimize the spray height objective function of spray deposition rate and coefficient of variance for the spray deposition. The spray process can be easily visualized and compared for different spray parameters. The indoor experiment setup was built to test and optimize the parameters of the overall system, which is flexible to verify the system. Afterward, the outdoor tractor-based equipment was designed to test the system for the field environment. The experimental result showed that 80% of the crop had a spray deviation from 0 mm to 28 mm and the proposed spraying system can reduce 46.8% usage of the chemical compared to the uniform spray method.